Short sleep and low milk intake are associated with obesity in a community of school aged children from Argentina. Issue 3 (19th February 2019) - Orden, Alicia B.; Lamarque, Muriel S.; Chan, Débora; Mayer, Marcos A.
Abstract: Objectives: Understanding the factors related to obesity during childhood allows for improved preventive actions specifically adapted to particular communities. The purpose of this study was to identify individual and familiar factors related to obesity in children. Methods: A cross‐sectional study was conducted in an urban community in Argentina during the years 2015‐2016. Weight and height were measured on a probabilistic sample of 1366 schoolchildren aged 6 to 12 years. BMI categories were established according to International Obesity Task Force (IOTF) cut‐offs. Data were analyzed using multivariate and logistic regression models. Independent variables corresponded to four domains: anthropometric, socioeconomic and demographic, nutritional, and energy balance. Results: Twenty percent of children were categorized as overweight (OW) and 12.2% were obese (OB). Parental IOTF grade was positively associated with childhood OW/OB (father B = 0.421 P = 0.000, OR = 1.52, 95% CI 1.24‐1.88; mother B = 0.498 P = 0.000, OR = 1.65, 95% CI 1.37‐1.97). The remaining variables were negatively associated with OW/OB: hours of sleep (B = −0.566 P = 0.001, OR = 0.57, 95% CI 0.41‐0.79), physical activity (B = −0.362 P = 0.017, OR = 0.70, 95% CI 0‐52‐0.94), and daily milk intake (B = −0.178 P = 0.045, OR = 0.84, 95% CI 0.70‐0.99). Parental IOTF predicted both OW and OB, while sleep hours predicted OW and physical activity predicted OB. Conclusions: Family should be considered the initial target for effective strategies to reduce obesity. Like physical activity, the promotion of milk and dairy intake, as well as sleep, may have a major role in obesity reduction because of their protective effects in this community.